Expression 2: "x" squared plus "y" squared plus "z" squared equals 1 left brace, "z" less than or equal to 0 , right brace left brace, "x" less than or equal to 0 , right bracex2+y2+z2=1z≤0x≤0
2
Expression 3: "x" squared plus "y" squared plus "z" squared equals 1 left brace, "z" greater than or equal to 0 , right brace left brace, "x" greater than or equal to 0 , right bracex2+y2+z2=1z≥0x≥0
3
Expression 4: "x" squared plus "y" squared plus "z" squared equals 1 left brace, "z" less than or equal to 0 , right brace left brace, "x" greater than or equal to 0 , right bracex2+y2+z2=1z≤0x≥0